Ab initio benchmark study of nonadiabatic S1-S2 photodynamics of cis- and trans-hexatriene - Komainda, Adrian; Lyskov, I.; Marian, C. M.; Köppel, Horst (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2016)
The dynamics of the nonadiabatically coupled lowest singlet excited states of cis- and trans-hexatriene are studied theoretically, in a comprehensive electronic structure and quantum dynamical investigation. At the ground state equilibrium geometry the relevant S2 and S1 states carry the A1 (Ag) and B2 (Bu) symmetry labels, for the cis (trans) isomer. Various high-level electronic structure methods are used, including the recently reparametrized DFT/MRCI method, and the results are critically compared. Key parameters of interest are the vertical energy gap and the strength of vibronic coupling between the interacting electronic states. To estimate their influence, suitable comparison calculations are performed. The results are used as the basis for quantum dynamical calculations on the UV absorption spectrum and electronic population transfer involving the S1 and S2 states. Up to nine nonseparable degrees of freedom are included in the calculations. The experimental UV absorption spectrum in the 5-5.2 eV energy range can be very well reproduced. The time-dependent wavepacket propagations reveal a population transfer on the order of 30-50 fs, which becomes increasingly complete with more degrees of freedom included in the calculation. The results are briefly compared with analogous data for the s-trans-butadiene system treated by some of us recently.
Gesehen am 14.05.2020